2017
DOI: 10.1016/j.jhep.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 3 is a target molecule linking hepatic steatosis to impaired glucose homeostasis

Abstract: Hepatic activating transcription factor 3 (ATF3) may play an important role in oxidative stress-mediated hepatic steatosis and the development of type 2 diabetes (T2D) in a Zucker diabetic fatty (ZDF) rat model and in human patients with non-alcoholic fatty liver disease (NAFLD). Therefore, ATF3 may be a useful biomarker for predicting the progression of NAFLD and the development of T2D. Furthermore, given the significant association between hepatic ATF3 expression and both hepatic steatosis and impaired gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…ORO staining demonstrated that ATF3 knockdown substantially attenuated PA‐induced lipid deposition in KO‐CON cells (Fig. A), which lent further support to previous in vivo conclusions . Furthermore, ATF3 knockdown partially relieved the exaggerated hepatosteatosis in IRF2BP2 ‐KO cells (Fig.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…ORO staining demonstrated that ATF3 knockdown substantially attenuated PA‐induced lipid deposition in KO‐CON cells (Fig. A), which lent further support to previous in vivo conclusions . Furthermore, ATF3 knockdown partially relieved the exaggerated hepatosteatosis in IRF2BP2 ‐KO cells (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Recently, a study published by Kim et al corroborated the fact that ATF3 is the key molecule linking hepatic steatosis and impaired glucose homeostasis . They demonstrated that hepatic ATF3 knockdown ameliorates metabolic dysfunction and inflammatory response in the Zucker diabetic fatty rat model . Moreover, a superinduction of ATF3 expression in liver is strongly correlated with type 2 diabetes and the grade of hepatic steatosis .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations